Pendampingan Rebranding Kemasan Produk Sayuran Segar (Keran Payung Bambu) Kelompok Wanita di RPTRA Payung Tunas Teratai dan Bambu Petung - Ani Nuraini; Nurminingsih Nurminingsih; Yeny Sulistyowati (Jurnal Pelayanan dan Pengabdian Masyarakat (Pamas), 2023)
According to a survey conducted by the Bank of Indonesia (BI) in July 2021, the Economic Conditions Index (IKE) was recorded at 67.1. IKE is composed of three components, namely the Current Income Index, Job Availability Index, and Durable Goods Purchase Index. On the other hand, the rapid expansion of internet access in Indonesia has been influencing consumer shopping trends, especially among those aged 25-38. Through various e-commerce platforms, consumers can access a wide range of products relevant to their daily lives, such as fresh fruits and vegetables. Therefore, it is essential to empower the community through robust and healthy entrepreneurial activities to support the local economy. This can be achieved through various means, including mentorship and training. The role of the community in the RPTRA Payung Tunas Teratai and Bambu Petung areas, through independent business activities, cannot rely on external entities. Hence, the development of micro and small-scale businesses accessible to the community is necessary. The community is encouraged to utilize available land for agriculture, including in RPTRA Payung Tunas Teratai and Bambu Petung. The types of vegetables produced are diverse, including water spinach, long beans, mustard greens, pumpkin, and more. The goal of these activities is to enhance marketing and income through rebranding. Special thanks to the Directorate General of Higher Education, Research, and Technology, Ministry of Education, Culture, Research, and Technology, for providing research funding in 2023, RPTRA Payung Tunas Teratai and RPTRA Bambu Petung, as well as the involvement of the Manpower, Transmigration, and Energy Office, Sub-district Office of Tourism and Creative Economy in East Jakarta, Satpel PPUKM, Satpel KPKP, and Satpel Dinsos in the Cipayung District, who participated and coordinated in the series of research activities. The activities took place on Friday, September 8, 2023, in RPTRA Payung Tunas Teratai in the Cipayung Sub-district and on Wednesday, September 12, 2023, in RPTRA Bambu Petung in the Bambu Apus Sub-district. A total of 79 participants attended, divided into two groups in RPTRA Payung Tunas Teratai and Bambu Petung. The results of this research were increased income, skills, and empowerment of partners. The research outputs include a national accredited journal publication (published in PAMAS, Sinta 4), electronic media coverage (Radar), video documentation (Website and YouTube URINDO), and additional intellectual property (Flyer) with certification. The impact of these activities on the achievement of higher education Key Performance Indicators (IKU) includes students gaining experience outside the campus (IKU-2), faculty members engaging in off-campus activities (IKU-3), and Faculty Work Results Used by the Community (IKU-5). Through these research activities, the beneficiary community members received information on how to process and package vegetables to prolong their shelf life and increase their market value. This series of research activities has proven to be highly beneficial, reducing losses for business operators through appropriate product packaging methods to maintain product freshness, durability, and appeal. Keywords: Rebranding, Fresh Vegetables, Women's Groups